PROFITABILITY OF PRODUCTION OF TABLE GRAPES IN REPUBLIC OF MOLDOVA - Tatiana IATISIN; Mihail CIOBANU; Angela TIMUS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Viticulture for table grapes is a branch of the agro-industrial complex, which possesses high adaptability to environmental conditions, relatively simple care and high economic efficiency, etc. For each economic agent, economic efficiency expresses the need for existing factors of production to be used under conditions of economic rationality, which means that unlimited needs are satisfied with increasingly limited resources throughout the economy. This paper presents the economic efficiency of table grape production. We can state that any economic activity must produce useful and qualitatively superior effects, satisfying the principle of rationality applied to the present time and to the future, thus ensuring the prerequisites for future efficiency. The research was carried out on the basis of data from the National Bureau of Statistics and reports from the Ministry of Agriculture and Food Industry, using methods of analysis, synthesis, tabulation and graphics. The vitivinicultural sector is and will remain an important one for the Republic of Moldova. High-quality grapes and wine are the calling card of our country, recognized internationally. Dynamically, in the years 2010-2018, the viticultural sector registered an average annual increase of 6.2% - the productivity of the vineyard per fruiting; 8.4% - the harvest of table grapes; 7.1% - export of table grapes.